Genetic engineering man and nature in transition - Heintze, Carl. (Nashville Nelson, 1974)
Discusses the importance of genetics in the balance of nature and recent research concerning man's influence on the control of genes.
Bibliography: p. 172-173.
Keywords: Genetic engineering -- Juvenile literature; Genetics